Three port versus four port laparoscopic cholecystectomy: a prospective comparative clinical study - Bari, Shams ul; Islam, Faheem ul; Rather, Ajaz A.; Malik, Ajaz A. (International Journal of Research in Medical Sciences, 2019)
Background: Although, traditional laparoscopic cholecystectomy is performed using four-port technique, various modifications were made to further enhance the advantages of laparoscopic cholecystectomy. Aim of the study is to compare the results of three-port and four-port laparoscopic cholecystectomy at single center in terms of technical feasibility, safety of the procedure, operative time, intra-operative complications, postoperative pain and post-operative analgesia requirement Methods: It was a prospective comparative study conducted in the department of surgery Skims Medical college Srinagar, India from July 2015 to March 2017. The study was performed on all adult patients with ultrasound documented cholelithiasis and gall bladder Polyposis. The total number of patients studied was 100 which were divided into two groups of 50 each. Results: The average operative time in three port group was 29.2 minutes (range, 15-37) compared to 30.66 minutes (range, 15-42) in four port group, which was statistically insignificant. The final visual analog scores for pain in the postoperative period was 2.30 vs 2.86 in three port and four port group respectively, with a P value=0.008, which was statistically significant. Conclusions: The three-port technique is as safe as the standard four-port technique and can be a viable alternative to four port cholecystectomy with an advantage of less pain and less analgesic requirement and better cosmetic results.